Abnormality positioning method and system based on panoramic video fusion - WANG XUN; WANG BEN; YIN ZHUYAN; GAO BAOLONG; SONG GAOSHUN (2025)
The invention relates to the technical field of anomaly positioning, and provides an anomaly positioning method and system based on panoramic video fusion. The method comprises the following steps: carrying out discrete video stream acquisition and return on a management and control area, and determining multiple paths of video streams; converting and clustering the multiple paths of video streams, and determining a preprocessed video stream; constructing a three-dimensional panorama fusion module, performing fusion splicing modeling on the preprocessed video stream, and determining a fusion panorama; carrying out abnormal event positioning and visual angle refinement based on the fused panorama, and determining abnormal positioning data; determining a spatial distribution field, performing spatial field calculation for the abnormal positioning data, and determining a target camera holder; and controlling the target camera holder, carrying out refined monitoring, and determining an abnormal positioning single